Metode Perolehan Dan Batas-Batas Wewenang Pemerintahan - Sri Nurhari Susanto (Administrative Law and Governance Journal, 2020)
Abstract Administrative authority can be obtained by means of attribution, delegation and mandate. Attribution is a way of obtaining the authority given or assigned to a particular position. Delegation authority is a form of transfer of authority, and mandate authority is the assignment authority. The limits of the use of administrative authority are measured based on the legality principle, both formal legality and material legality. Formal legality relates to powers and procedures and material legality relating to the purpose of granting authority by laws and regulations. Flaw in power will result in government actions being null and void, while procedural defects can be invoked, but not by law. Keywords: governmental authority,  obtained by means , limitations